Clinico-epidemiological profile of dengue cases in a Medical College Hospital, Bengaluru, Karnataka, India - V., Srividya; N., Kruthika (International Journal Of Community Medicine And Public Health, 2017)
Background: Medical college hospital being a tertiary care center receives a significant number of dengue cases from within and outside the catchment area and provides a good opportunity to study the clinical and epidemiological features of dengue infection, its prognosis and outcome so as to institute prompt preventive and control measures. The objective was to describe the clinico-epidemiological features of dengue cases admitted to pediatric ward at a Medical College Hospital, Bengaluru, Karnataka, India. Methods: Cross-sectional study of 140 cases positive for NS1Ag, IgM and/or IgG by dengue rapid immuno-chromatographic card test, admitted in pediatric ward during June to August 2013 at Rajarajeswari Medical College and Hospital. Results: Majority of the patients were from rural area. Fever was present in all 140 cases. Vomiting followed by headache were the common presenting symptoms. Of the 140, 50% cases were classified as dengue fever without warning signs, 46.4% as dengue fever with warning signs and 3.6% as severe dengue. Thrombocytopenia was present in 77.1%, leucopenia in 47.9%, and raised haematocrit in 52.1% of cases. Mortality rate was 0.71%. Conclusions: Children above 5 years of age were most commonly affected age group. About 5 (3.6%) of the patients belonged to severe dengue category according to revised WHO Dengue Case Classification.